Punching shear in eccentrical loaded flat slabs - Moreno, Carlos (2012)
The effect of the eccentricity of loading on the behaviour of slab-column connections without or with headed studs as shear reinforcement is experimentally investigated. Normal and fibre reinforced concrete slabs were experimentally tested. Test results are compared with code provisions and with numerical simulation analyses.